2006
DOI: 10.1523/jneurosci.3907-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions Preferentially Engage an Auditory–Motor “Mirror” System

Abstract: Social interaction relies on the ability to react to communication signals. Although cortical sensory-motor "mirror" networks are thought to play a key role in visual aspects of primate communication, evidence for a similar generic role for auditory-motor interaction in primate nonverbal communication is lacking. We demonstrate that a network of human premotor cortical regions activated during facial movement is also involved in auditory processing of affective nonverbal vocalizations. Within this auditory-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
212
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(242 citation statements)
references
References 41 publications
25
212
2
3
Order By: Relevance
“…First, it has been reported that a patient with Foix-Chavany-Marie syndrome, a form of pseudo bulbar palsy resulting from bilateral opercular lesions, was unable to yawn voluntarily (whether spared involuntary yawning was spontaneous and/or contagious is unclear; Laurent-Vannier, Fadda, Laigle, Dusser, & Leroy-Malherbe, 1999). Second, and more convincingly, recent f MRI investigations of mouth movements have shown that very proximal, if not the same, regions of the pIFG in BA44 are activated when participants are asked to smile (Warren et al, 2006), imitate facial expressions (Lee, Josephs, Dolan, & Critchley, 2006;van der Gaag, Minderaa, & Keysers, 2007), manipulate small objects with their lips , listen to pure mouth sounds (e.g., crunching a piece of candy with the teeth, kissing, gurgling, crunching potato chips, finishing a can of soft drink with a straw; Gazzola et al, 2006), or listen to nonverbal human vocalizations (Warren et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…First, it has been reported that a patient with Foix-Chavany-Marie syndrome, a form of pseudo bulbar palsy resulting from bilateral opercular lesions, was unable to yawn voluntarily (whether spared involuntary yawning was spontaneous and/or contagious is unclear; Laurent-Vannier, Fadda, Laigle, Dusser, & Leroy-Malherbe, 1999). Second, and more convincingly, recent f MRI investigations of mouth movements have shown that very proximal, if not the same, regions of the pIFG in BA44 are activated when participants are asked to smile (Warren et al, 2006), imitate facial expressions (Lee, Josephs, Dolan, & Critchley, 2006;van der Gaag, Minderaa, & Keysers, 2007), manipulate small objects with their lips , listen to pure mouth sounds (e.g., crunching a piece of candy with the teeth, kissing, gurgling, crunching potato chips, finishing a can of soft drink with a straw; Gazzola et al, 2006), or listen to nonverbal human vocalizations (Warren et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, more studies are needed on the explicit and attentive processing of nonverbal vocal expressions. Most of the studies on the processing of nonverbal vocal expression use an implicit (Belin et al, 2008a;Fecteau et al, 2005;Morris et al, 1999) or a passive listening approach (Warren et al, 2006). This makes it difficult to compare functional activations for the attentive (explicit) and preattentive processing (implicit) of nonverbal emotional expressions and to completely discern the effects of the attentional focus and the medium of vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of the article.) (Pichon and Kell, 2013) and the caudally adjacent premotor cortex (Warren et al, 2006) in the preparation and execution of (vocal) motor outputs in response to perceived emotional prosody. Unlike nonverbal expressions, emotional prosody more often occurs in conversational settings, and thus a close anatomical link between the posterior IFC and the ventral premotor cortex might support perception-action cycles in emotional conversations.…”
Section: The Medium Of Vocal Expressionsmentioning
confidence: 99%
“…Also, when speech signals are distorted, the motor cortex is markedly activated [45,46] . Interestingly, non-verbal signals can activate motor areas [31,47] , and there is no difference in activation magnitude in the motor cortex between perceiving speech and perceiving nonverbal sounds [31] . Some studies have further shown that blurred speech causes even stronger activation in the bilateral premotor cortex, compared to clear speech [45] and perceiving a foreign language causes larger activation in the motor cortex than the native language [25] .…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 97%